PENGEMBANGAN MEDIA PEMBELAJARAN MATEMATIKA BERBASIS APLIKASI MOBILE LEARNING BERBANTUAN I-SPRNG PADA MATERI PHYTAGORAS - Hanifah, Ririn; Sari, Dwi Ivayana (Prismatika: Jurnal Pendidikan dan Riset Matematika, 2021)
The implementation of distance learning that was applied during the Covid-19 pandemic simultaneously in all corners of the country has had a different impact on each student. Students who live in urban areas may not experience many obstacles, but it is different from students who live in rural areas. There are many places in the village that are difficult to reach by signals, causing students to be constrained in the online learning process. This study aims to present a mobile learning-based mathematics learning media that can be accessed offline so that it can overcome the problems of students who are in signal-difficult areas. This research is a research and development study using the ADDIE development model. This model has five stages of development, namely Analysis, Design, Development, Implementation, and Evaluation. The research was conducted with alpha trials and beta trials. Respondents for the alpha trial were validators and teachers. Respondents for the beta trial are students.The results of research conducted with alpha trials and beta trials indicate that this medium is valid and worthy of use.